Collective action in the management of canal irrigation systems: The Doho rice scheme in Uganda - Sserunkuuma, Dick; Ochom, Nicholas; Ainembabazi, John H. (International Food Policy Research Institute, 2009)
Devolution of natural resource management (NRM) from governments to user groups has often been justified on the premise that local users have comparative advantage and self-interest over government agents in managing and monitoring such resources. Examples of successful collective action in various areas have also fuelled the drive to devolve NRM to local users (Meinzen-Dick, Raju, and Gulati 2000). It is on this basis that the government of Uganda decided to devolve management of the irrigation system at the Doho Rice Scheme (DRS) to the DRS Farmers’ Association. The operation and maintenance of such irrigation schemes requires a high degree of coordination, yet with devolution, the state withdraws from this role. Therefore, the success of the devolution policy in improving NRM is highly dependent on the ability and willingness of the farmers to organize successful collective action, but this outcome cannot be assumed—the more so when devolution calls for more time and cash contributions from the farmers. The need to examine farmers’ willingness to participate in collective action after the withdrawal of government support motivated this case study, because it is critical for effective implementation of the devolution policy and the development of strategies for sustainable collective action at DRS.